2009
DOI: 10.1159/000213757
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of COPD on Mortality and Severity Scoring in Community-Acquired Pneumonia

Abstract: Background: Chronic obstructive lung disease (COPD) is a frequent co-morbidity in patients hospitalised with community-acquired pneumonia (CAP). In recent retrospective studies, higher mortality in patients with CAP and COPD was found. Objectives: The aim of the study was to determine the 30-day mortality and to evaluate the differences in CAP severity scoring in hospitalised patients with COPD. Methods: A subanalysis of a randomized clinical trial was performed. Results: A total of 262 patients with CAP were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 48 publications
4
39
2
Order By: Relevance
“…In one prospective Spanish study, the mortality was 8%, which did not seem to be in excess of the rates reported for the general population [3]. Accordingly, in a subanalysis of a randomised clinical trial, the mortality was 8% and was not increased in patients with COPD hospitalised with CAP.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In one prospective Spanish study, the mortality was 8%, which did not seem to be in excess of the rates reported for the general population [3]. Accordingly, in a subanalysis of a randomised clinical trial, the mortality was 8% and was not increased in patients with COPD hospitalised with CAP.…”
Section: Discussionmentioning
confidence: 83%
“…Whereas two studies do not support COPD as a risk factor for death [3,5], two other studies did show an excess mortality of CAP in patients with COPD [5,6].…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Four studies 15,17,19,26 were multicenter studies, and two studies 16,29 analyzed data from the nationwide databases. Of these cohort studies, five were prospective and four 17,18,26,28 were retrospective. All cohort studies ascertained the diagnosis of CAP based on chest radiographic findings, whereas the two case-control studies identified the cases of CAP according to the International Classification of Diseases (ICD-10) codes.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…[15][16][17] Nevertheless, many other studies demonstrated that COPD was not associated with significant mortality, longer hospital stay and more intensive care unit (ICU) admission. [18][19][20] Thus, the aim of this systematic review and metaanalysis was to investigate whether COPD was associated with increased mortality and morbidity in patients with CAP.…”
Section: Introductionmentioning
confidence: 99%